Legal Study of Bankruptcy in Indonesia: Study of Decision Number 36/Pdt.Sus-Pailit/2020/PN Niaga Jkt.Pst - Rahmadani, Gema; Putri, Elfirda Ade; Fitriani, Fitriani (Universitas Medan Area, 2025)
This study aims to analyze the legal position of debtors and creditors in bankruptcy cases and assess the judge's considerations in Decision Number 36/Pdt.Sus-Pailit/2020/PN Niaga Jakarta Pusat, particularly the extent to which these considerations are in accordance with applicable legal norms. The research method used is normative juridical, with an approach based on legislation, court decisions, and legal literature related to bankruptcy. Data was obtained through document studies and court decisions, then analyzed qualitatively to assess the balance of debtor and creditor rights and the consistency of the decision with Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. The results of the study show that debtors who are declared bankrupt experience restrictions on their property rights, while creditors obtain legal certainty through the mechanism of appointing a curator and distributing assets. The judges' considerations emphasize the examination of evidence, the right to be heard, and the principle of substantive justice, so that the decisions are generally consistent with applicable legal norms. This research contributes to the understanding of bankruptcy law practices in Indonesia and serves as a reference for efforts to resolve disputes between debtors and creditors in a fair and transparent manner.